Pengaruh Bargaining Power dan Kegiatan Usaha Nasabah terhadap Penentuan Nisbah Bagi Hasil Pembiayaan Mudharabah - Bahmid I Magi; Herni Nuraeni; Yudhy Yudhy; Eni Nuraeni (Jurnal Dimamu, 2022)
This study aims to find out how the influence of bargaining power and customer business activities on determining the ratio of mudharabah financing profit sharing at Bank BSI KC Suniaraja Bandung both individually and simultaneously. The object of research used is mudharabah financing at Bank BSI KC Suniaraja Bandung. The type of research is associative quantitative with primary data types, while data collection techniques are in the form of observations, interviews, questionnaires and literature studies. The population is 113 mudharabah financing customers. The results showed that there was a significant influence of bargaining power on determining the profit sharing ratio of mudharabah mudharabah financing at Bank BSI KC Suniaraja Bandung where the results of the thitung test were > ttabel (8,330> 2,012), there was a significant influence of customer business activities on determining the ratio of sharing the mudharabah mudharabah financing at Bank BSI KC Suniaraja Bandung where the results of the thitung test were > ttabel (5,351>2,012), and simultaneously there is a significant influence between bargaining power and customer business activities on determining the profit sharing ratio of mudharabah financing at Bank BSI KC Suniaraja Bandung where the calculation result is > ftabel (10,873>3.18).